Combined Cutaneous Sarcoma: Pleomorphic Liposarcoma and Conventional Osteosarcoma—The So-Called Malignant Mesenchymoma - David Parada; Karla B. Peña (Case Reports in Pathology)
Malignant mesenchymoma is combined soft tissue tumors of mesenchymal origin. Cutaneous combined sarcomas are exceedingly rare. We report the case of an 81-year-old woman who presented a left cutaneous mass. She underwent a wide local excision. Histopathological and immunohistochemical studies were consistent with the diagnosis of combined pleomorphic liposarcoma and conventional osteosarcoma (malignant mesenchymoma). Although it is extremely rare, this case suggests that combined sarcoma should be considered in the differential diagnosis of undifferentiated pleomorphic neoplasms.